Cyclin dependent Kinases as potential therapeutic targets for atherosclerosis - Rostam, Muhamad Ashraf; Piva, Terence J.; Osman, Narin; Little, Peter J. (2015)
Cardiovascular disease is the leading cause of death among adults worldwide and atherosclerosis is the major underlying pathology. The pre-inflammatory stage of atherosclerosis is associated with proteoglycan glycosaminoglycan (GAG) chain hyper-elongation that results in increased proteoglycan (PG) binding to low density lipoprotein (LDL). Elevated GAG synthesizing enzyme mRNA expression has been shown to be linked to in vivo atherosclerosis development. Transforming Growth Factor-β (TGF-β) is associated with atherosclerosis and mediates GAG chain hyper-elongation. The specific GAG synthesizing enzymes and the signalling pathways are unclear. TGF-β signals through phosphorylation of Smad 2/3 at its C-terminus and it can also lead to other serine/threonine kinases, including ERK, to phosphorylate Smad2 in the linker region. This leads to TGF-β mediated PG hyper-elongation in human vascular smooth muscle cells (VSMC). Little is known regarding the involvement of CDK in TGF-β mediated PG synthesis in human VSMC. Understanding this signalling pathway facilitates the identification of a therapeutic target to prevent atheroslcerosis